2006
DOI: 10.1063/1.2335798
|View full text |Cite
|
Sign up to set email alerts
|

Deep acceptor states in ZnO single crystals

Abstract: The authors report the observation of both acceptor- and donorlike defects in ZnO by deep level transient spectroscopy. The observation is facilitated by using a p-n junction allowing the injection of holes and electrons. The junction is realized by implanting a n-conducting ZnO wafer grown by pressurized melt growth with nitrogen ions. The authors found the commonly observed donorlike defects E1 and E3 and two acceptorlike defects A2 and A3, as well as a broad acceptorlike defect band. The thermal activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 26 publications
2
45
0
Order By: Relevance
“…16 The hole trap H3, with activation energy of 0.35 eV, could be related to transition metals in the p-Si, or Zn that might have diffused into the p-Si during growth of the ZnO films. 17 It should also be mentioned that a Li-acceptor-related hole trap A 3 , with activation energy of 0.28 eV and capture cross section of ϳ10 −16 cm 2 , was reported in pressurized melt-grown ZnO using a p − n junction diode formed by N + -implantation; 8 on the other hand, we have no evidence for Li in our sample. The hole trap H4, with an activation energy of 0.48 eV, could also be due to transition metals in p-Si.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…16 The hole trap H3, with activation energy of 0.35 eV, could be related to transition metals in the p-Si, or Zn that might have diffused into the p-Si during growth of the ZnO films. 17 It should also be mentioned that a Li-acceptor-related hole trap A 3 , with activation energy of 0.28 eV and capture cross section of ϳ10 −16 cm 2 , was reported in pressurized melt-grown ZnO using a p − n junction diode formed by N + -implantation; 8 on the other hand, we have no evidence for Li in our sample. The hole trap H4, with an activation energy of 0.48 eV, could also be due to transition metals in p-Si.…”
Section: Resultsmentioning
confidence: 55%
“…A recent DLTS study has revealed deep acceptor states ͑hole traps͒ in ZnO single crystals using a novel p − n junction formed by N + implantation. 8 In that study, an N + -implanted p-ZnO layer was employed for injecting holes. Here, we present a DLTS investigation of a ZnO:N thin film incorporated into a p − n junction diode.…”
Section: Introductionmentioning
confidence: 99%
“…However, the electron irradiation introduces a new trap with an activation energy of 0.15 eV, and other traps of energy 0.30 and 0.80 eV, respectively. From a comparison of these results with positron annihilation experiments and density functional theory, we conclude that the 0.15-eV trap may be related to V Zn 4,5 Both materials contained two prominent defects: E1 at E C − 0.12 eV and E3 at E C − 0.29 eV. In VP ZnO, E1 is the primary defect, while in MLT ZnO, E3 dominates.…”
Section: G C Farlowmentioning
confidence: 84%
“…techniques. [14][15][16][17][18][24][25][26][27] However, the microscopic origins of this defect are not clear as yet. Annealing ZnO samples in different ambient increases the intensity of the DLTS peak for the E3 defect (Figure 3(a)), with the highest intensity being observed for the Ar þ O 2 annealed samples.…”
Section: Emission Properties Of E3mentioning
confidence: 99%